Studi Perbandingan Kewenangan Kejaksaan Republik Indonesia Dengan Kejaksaan Malaysia Dalam Penanganan Perkara Tindak Pidana Korupsi - Nada Ulya Qinvi; Alfitra Alfitra (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study aims to explain the role of the Attorney General of the Republic of Indonesia and the Malaysian Attorney in corruption, as well as the similarities and differences between the authority of the Attorney General of the Republic of Indonesia and the Attorney General of Malaysia in handling corruption cases. This research uses qualitative research. In this study the method of data collection is done by the study of literature. Data that has been collected and analyzed using descriptive-qualitative methods. The approach used in this research is the statutory approach and conceptual approach. The results of this study indicate that the similarity between the authority of the Republic of Indonesia Prosecutor's Office with the Malaysian Prosecutor's Office is the role of the Prosecutor as the Public Prosecutor, while the distinguishing authority of the Prosecutor's Office of the Republic of Indonesia and the Prosecutor's Office is Malaysian authority in the field of prosecution.Keywords: Comparison, Authority, Prosecutor, Corruption